The playing position significantly influences return to sports and recurrences after an arthroscopic Bankart repair in competitive rugby players - Pasqualini, Ignacio (2022)
Background: The purpose of our study was to investigate the influence of the different rugby playing positions on return to sports, functional outcomes, and recurrences after an arthroscopic Bankart repair. Methods: A total of 88 rugby players were treated for anterior shoulder instability in our institution between 2010 and 2018. Functional outcomes, return to sports, recurrences, complications, and revisions rates were evaluated according to the playing position. Results: Overall, 73.8% of the patients returned to rugby and 60% returned at the same level as before the injury. The tight forwards and outside backs experienced a significant decrease in their competitive level after surgery, and showed the lowest functional outcomes. The tight forwards and outside backs showed a statistically significant increase in recurrence and revision rates, and an OR for recurrence of 12.8 and 9.6, respectively. Discussion: The playing position significantly influenced return to sports and recurrences after an arthroscopic Bankart repair in competitive rugby players. Specifically, the tight forwards and outside backs have returned to a lower level than they had before surgery, showed the lowest functional outcomes, and a significant increase in recurrences and revisions rates than the other groups.